상복부 초음파 영상에서 간경변증 환자군과 대조군의 담석증 유병률 연구 - 조청현(Cheong-Hyeon Jo); 김용권(Yong-Gwon Kim); 유세종(Se-Jong Yoo); 배석환(Seok-Hwan Bae) (방사선기술과학, 2023)
This study aimed to understand the correlations of prevalence and relevant variables of cholelithiasis with a group of cirrhosis patients and a control group targeting the subjects who received the abdomen ultrasonography from K university hospital in Daejeon Metropolitan City from January 1st 2019 to December 31st. And the results are as follows. First, the group of cirrhosis patients showed relatively higher prevalence of cholelithiasis than the control group as ordinary people, which showed statistically significant differences. Second, in the control group, there were statistically significant differences in the occurrence of cholelithiasis with respect to age. Conversely, in the cirrhosis patient, there was no statistically significant association observed with age; nonetheless, age itself exhibited statistical significance. Third, according to sex, the prevalence was not statistically significant in both group of cirrhosis patients and control group. Fourth, in each degree and cause of subdivided cirrhosis, the correlation was only shown in each degree. In the results of this study, the cirrhosis patients showed high correlation with the incidence of cholelithiasis, and the control group showed the high correlation with the incidence of cholelithiasis according to age.